Health behaviors, health, sociodemographic factors, and school success in adolescence as risk factors for injury deaths: a longitudinal study - Teuho, Alisa; Ponkilainen, Ville; Koivusilta, Leena; Rimpelä, Arja; Mattila, Ville M. (BMC public health, 2025)
Background Injuries are a substantial cause of mortality in young adults. Previous longitudinal studies on the impact of adolescent health behaviors, health, sociodemographic factors, and school success on injury deaths are lacking. We examined the influence of these factors in adolescence on later injury death. Methods We conducted a population-based longitudinal study with an average 26-year follow-up, using questionnaire data from the Adolescent Health and Lifestyle Survey (AHLS) and register data. Adolescents aged 14, 16, or 18 years who answered the survey between 1981 and 1997 were included. A total of 47 326 individuals responded to the survey. Causes of death were obtained from the Finnish official Cause-of-Death Register. Cox regression model was used to analyze the associations between explanatory variables and injury death. Adjusted hazard rations (aHR) and 95% confidence intervals (CI) were computed. 14-year-olds and 16–18-year-olds were analyzed separately by sex. Results We identified 550 injury deaths, 432 in men and 118 in women. The mean age at death was 30 years. Drinking style (recurring drunkenness 14-year-old girls aHR 4.35 CI 1.00–19.02 and boys aHR 4.02, CI 1.62–10.00; 16–18-year-old girls aHR 2.63, CI 1.13–6.13 and boys aHR 1.70, CI 1.07–2.71) was associated with injury death in all subgroups. Smoking (girls aHR 2.00, CI 1.21–3.33 and boys aHR 1.86, CI 1.42–2.44) and stress symptoms (two or more/day girls aHR 2.34, CI 1.32–4.14 and boys aHR 2.07, CI1.39–3.07) were associated with injury death in 16–18-year-olds. Not living with both parents also increased the risk of injury death in boys. Conclusion Our findings suggest that adolescents who drift into risky health behavior and struggle with stress symptoms are at higher risk for injury death later in life. More support should, therefore, be allocated to these groups during adolescence.